Governance Structures and Decision-Making Roles in Inflation-Targeting Central Banks - Tuladhar, Anita (IMF Working Papers; Working Paper ;, 2005)
This paper surveys decision-making roles of governing bodies of central banks that have formally adopted inflation targeting as a monetary framework. Governance practices seek to balance institutional independence needed for monetary policy credibility with accountability required to protect democratic values. Central bank laws usually have price stability as the primary monetary policy objective but seldom require an explicit numerical inflation target. Governments are frequently involved in setting targets, but to ensure operational autonomy, legal provisions explicitly limit government influence in internal policy decision-making processes. Internal governance practices differ considerably with regard to the roles and inter-relationships between the policy, supervisory, and management boards of a central bank.